2008
DOI: 10.1128/jb.01659-07
|View full text |Cite
|
Sign up to set email alerts
|

Swarming ofPseudomonas aeruginosaIs a Complex Adaptation Leading to Increased Production of Virulence Factors and Antibiotic Resistance

Abstract: In addition to exhibiting swimming and twitching motility, Pseudomonas aeruginosa is able to swarm on semisolid (viscous) surfaces. Recent studies have indicated that swarming is a more complex type of motility influenced by a large number of different genes. To investigate the adaptation process involved in swarming motility, gene expression profiles were analyzed by performing microarrays on bacteria from the leading edge of a swarm zone compared to bacteria growing in identical medium under swimming conditi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

18
357
4
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 338 publications
(380 citation statements)
references
References 53 publications
18
357
4
1
Order By: Relevance
“…This type of adaptive resistance is reminiscent of the non-genetic resistance that some bacterial species exhibit when engaging in collective swarming motility (Kim et al, 2003;Overhage et al, 2008;Butler et al, 2010;Roth et al, 2013). Nonresistant swarming Salmonella enterica populations were previously shown to migrate from an antibiotic-free agar surface onto an agar surface containing lethal doses of an antibiotic (Butler et al, 2010).…”
Section: Resultsmentioning
confidence: 99%
“…This type of adaptive resistance is reminiscent of the non-genetic resistance that some bacterial species exhibit when engaging in collective swarming motility (Kim et al, 2003;Overhage et al, 2008;Butler et al, 2010;Roth et al, 2013). Nonresistant swarming Salmonella enterica populations were previously shown to migrate from an antibiotic-free agar surface onto an agar surface containing lethal doses of an antibiotic (Butler et al, 2010).…”
Section: Resultsmentioning
confidence: 99%
“…In contrast, no significant difference was observed between the biofilms of a mucoid P. aeruginosa strain and those of an aprA deletion mutant, indicating that AprA does not have an important function in the development and/or maintenance of the 3D structure of mucoid P. aeruginosa biofilms (Sarkisova et al, 2005). Recently, transcriptome analysis of P. aeruginosa has shown a 4.9-fold increase in lasB expression under swarming conditions (Overhage et al, 2008), indicating a potential role for LasB in the highly complex swarming process. Similarly, in Bacillus subtilis it has been shown that swarming motility is enhanced by the expression of extracellular protease activity (Connelly et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Other mechanisms such as the development of swarming colonies, the stringent response, i.e. response to nutrient limitation, and the formation of multiresistant subpopulation of persistent cells contribute to the multidrug-resistant phenotype [21][22][23] . Furthermore, P. aeruginosa is versatile in the development or acquisition of new mechanisms of resistance to antibiotic treatment.…”
Section: Discussionmentioning
confidence: 99%